A Pilot Study on the Effect of Virgin Coconut Oil on Serum Lipid Profile and HS CRP Level Among Post-Acute Coronary Syndrome Patients: A Randomized Controlled Trial - Sharifah Shafinaz, Sh Abdullah; Chan, Chong Mei; Khatijah Lim, Abdullah *; Imran, Zainal Abidin; Yap, Bee Wah (Marmara University, 2022)
Background: Virgin Coconut Oil (VCO) is beneficial for human health. Introducing VCO is cost-effective in Acute Coronary Syndrome (ACS) management compared to currently available medication. This study examines the influence of VCO on serum lipid profiles and hs CRP level among ACS patients. Methods: A randomized single-blinded study was conducted from March 2018 to May 2018 among 70 ACS patients. The random sampling technique was used to allocate participants in the control and intervention groups respectively. Participants in Group A received one bottle containing 100 pieces of virgin coconut oil soft gels and were required to ingest 5 soft gels (5ml/5g) twice per day. Group B participants received routine treatment and statin. Changes in serum lipid profiles were identified using a paired t-test and an independent t-test. Results: The 70 ACS patients were 51 years old and older and were mostly male. The total cholesterol level and Low-Density Lipoprotein Concentration (LDL-C) were reduced from baseline for 30 days. Most participants (68%) reported feeling better doing daily activities although some (22%) reported feeling worse from consuming virgin coconut oil due to its oily odour and slightly oily taste during eructation. Conclusion: Virgin coconut oil was able to reduce serum lipid profile based on total cholesterol, triglyceride, and LDL-C through its consumption of 5 grams per day for 30 days. Virgin coconut oil may have a positive effect on cholesterol levels and other cardiovascular risk factors.